Pyrolysis of de-oiled yeast biomass of Rhodotorula mucilaginosa IIPL32: Kinetics and thermodynamic parameters using thermogravimetric analysis. (November 2021) - Banerjee, Ayan; Vithusha, T.; Krishna, Bhavya B.; Kumar, Jitendra; Bhaskar, Thallada; Ghosh, Debashish
Graphical abstract: Highlights: Deoiled yeast biomass exhibited decomposition in three stages. Conventional & advanced methods indicated 87 & 216 KJ/mol as effective activation energy. De-oiled yeast pyrolysis exhibited random nucleation followed by third order kinetics mechanism. Thermodynamic parameters suggested de-oiled yeast can be a potential feedstock for valorisation. Abstract: The increasing demand for natural resources has highlighted the need to search for unutilized carbon resource that satisfy the demand and pose a minor threat to the environment. Yeast is a microbe with large industrial applications, and the biomass leftover after fermentation needs utilization for achieving increased efficiency. De-oiled yeast biomass (DYB), the residue after yeast lipid extraction, has not yet been evaluated for its potential application in the pyrolysis process. The present study was performed to understand its detailed pyrolysis kinetics. The observed activation energy (87–216 KJ/mol), random nucleation mechanism, pre-exponential factor (7.87 × 10 31 –3.24 × 10 31 /min), and thermodynamic profile showed the DYB pyrolysis process to be feasible. .